The relevance of HLA class II histocompatibility gens in predicting the risk of developing several bullous dermatoses - Marianna Drozhdina; Sergey Vladimirovich Koshkin; Pavel Grigorievich Chuprakov (Vestnik Dermatologii i Venerologii)
Background. Bullous dermatoses are a group of severe heterogeneous diseases that are potentially life threatening and significantly worsen its quality.